Masters of the steppe : the impact of the Scythians and later nomad societies of Eurasia : proceedings of a conference held at the British Museum, 27-29 October 2017 - Pankova, Svetlana (Curator); Simpson, St John (Archaeopress Archaeology, 2020)
'Masters of the Steppe' consists of 45 papers presented at a major international conference held at the British Museum in 2017 on the occasion of the BP exhibition 'Scythians: Warriors of Ancient Siberia', both conference and exhibition being jointly organised with the State Hermitage Museum. There are 58 contributors and co-authors from 16 countries, mostly from Russia, Ukraine and Kazakhstan, but also America, Britain, France, Germany, China and Mongolia. The papers range from new archaeological discoveries, results of scientific research and studies of museum collections to reconstructions of social elites, the phenomenon of monumental tomb construction, and 'Animal Style' art.